Factors Affecting Households Expenditure in Central Region by Income Groups - Suratthanamethakul, Parisa; Sinsomboonthong, Saichon (Thai Journal of Science and Technology, 2021)
The main purpose of this study was to examine the factors affecting expenditure of households in the central region classified by income groups as low-income, middle-income, and high-income households. Data were obtained from the household socio-economic survey in 2019, conducted by National Statistical Office of Thailand. There were 12,932 households in central region. The study population in each province of the central region had similar nature of characteristics. Total of 30 independent variables were included in this study. The data were analyzed using multiple regression method. Factor analysis was applied to reduce large number of explanatory variables, to remove multicollinearity problems. The results of the study revealed that, the significant factor affecting expenditure of households in all income groups were number of family members and return on saving money. Moreover, the significant factor affecting expenditure of households at least 2 income groups consist of work status of head of household, administrative area, welfare received of government personnel, marital status of head of household, elderly household members receiving welfare government and number of members receiving other government fund.